Comparative Analysis of Constitutional Protections for Freedom of Speech in Democratic States - Wiwi Winarti (Asian Journal of Multidisciplinary Research, 2025)
This study examines constitutional protections for freedom of speech in democratic states through a comparative legal approach. Using a systematic literature review method, this research analyzes 23 selected scholarly articles to identify key patterns, similarities, and differences in constitutional frameworks, judicial interpretation, and contemporary challenges. The findings reveal that while freedom of speech is universally recognized as a fundamental right, its scope and limitations vary significantly across jurisdictions due to differences in legal traditions, constitutional design, and socio-political contexts. Judicial interpretation plays a critical role in shaping the practical application of this right, particularly through doctrines such as proportionality and balancing tests. In addition, the study highlights the ongoing challenge of reconciling freedom of speech with competing interests, including national security, public order, and the protection of individual rights. The research also underscores the impact of digitalization, which introduces new complexities in regulating online expression and challenges traditional constitutional frameworks. This study contributes to the development of comparative constitutional law by offering an integrative analysis that combines doctrinal and contextual perspectives. It provides valuable insights for policymakers, legal practitioners, and scholars in strengthening democratic principles and ensuring effective protection of freedom of speech in an evolving global landscape.